Insulin Therapy Increases the Risk of Hypokalemia and Arrhythmia in Diabetic Patients with Coronary Heart Disease: A Retrospective Study in Wahidin Sudirohusodo General Hospital: Terapi Insulin Meningkatkan Risiko Hipokalemia dan Aritmia pada Penderita Diabetes dengan Penyakit Jantung Koroner: Studi Retrospektif di RSU Wahidin Sudirohusodo - Hastuti Tajuddin; Elly Wahyudin; Yulia Yusrini Djabir; Firzan Nainu; Latifah Rahman (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2022)
Background: Cardiovascular disease is the most common cause of morbidity and mortality in diabetic patients. Patients with Diabetes Mellitus (DM) often require insulin therapy to control hyperglycemia, yet, it is associated with the risk of hypokalemia and dysrhythmia. Objectives: To evaluate the prevalence and the risk of hypokalemia and arrhythmia due to insulin therapy in DM patients with Coronary Heart Disease (CHD) comorbidity. Material and Methods: The study was conducted retrospectively based on medical record data from January 2021 to December 2021 in Wahidin Sudirohusodo general hospital. The inclusion criteria include the out-hospital patients diagnosed with DM with CHD comorbidity. The patients were divided into 2 groups, those who received insulin and those who received oral antidiabetic drugs (OAD). Hypokalemia was defined if an electrolyte characterized by a low serum potassium concentration with a normal range of 3.5 – 5.0 mEq/L. Arrhythmia was defined if abnormal changes in a regular heartbeat, including an irregular heartbeat, a skipped heartbeat, a fast heart rate (tachycardia), or a slow heart rate (bradycardia). Results: The data were obtained from 322 patients’ medical record, 161 was treated with insulin, and 161 received OAD. The insulin-treated patients had a significantly lower blood potassium level compared to the OAD group. The insulin group had 63,40% incidents of hypokalemia, while in the OAD group only 16,80% experienced hypokalemia (p<0.05). The presence of arrhythmia was detected in 63,40 % of insulin-treated patients, while only 29,80% had arrhythmia in the OAD group (p<0,05). Conclusions: Insulin Therapy in DM patients with coronary heart disease can increase the incidence of hypokalemia, which may result in arrhythmia in patients with coronary heart disease.